(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Postinfectious glomerulonephritis (PIGN) remains one of the most common causes of acute glomerulonephritis in children worldwide. Although the disease generally has a favorable prognosis, some pediatric patients may develop acute kidney injury (AKI) and long-term renal impairment. Early identification of risk factors associated with kidney damage is important for improving clinical management and preventing chronic kidney disease. These findings highlight the importance of early identification of clinical and laboratory predictors of kidney damage in children with PIGN. Recognizing high-risk patients may improve clinical outcomes and guide long-term monitoring strategies.